Religious architecture a study on the development of christian churches in Davao region - Rios, Kyle Mae E. (2020)
The study is focused on the assessment of the two components of architecture, Order and Complexity, in Catholic and Apostolic denomination. The result of this research will be able to identify the characteristic of the ideal church aesthetic from the lay-person?s perspective, using the Birkhoff?s Aesthetic Measure. This will uplift the definite characteristic of catholic and apostolic church which will add a sense of place and meaning for the people under the denominations. The research will also serve as the documentation of the catholic and apostolic churches in Davao region. The noticeable lack of detailed documentation and research study of the Apostolic religion is one of the main motivations of this research. Therefore, the result will help the people understand the religion more through its documented architectural characteristics. The main method of the study is the acquiring of the qualitative data through a case study descriptive research. The qualified churches were required to have the construction finished and were still functioning as a house of worship. Subsequently, the research was focused on the catholic and apostolic churches in Davao region. Therefore, three (3) randomly selected Roman Catholic churches around Davao region were selected and as well as twelve (12) Christian churches were selected subdivided into five (4) sectors namely; United Pentecostal Church Inc., Four Square Gospel Church, United Church of Christ Philippines and Bible Baptist Church. The second phase of the research is the aesthetic assessment of the researcher using the Birkhoff?s Aesthetic Measure Guideline. Then a combination of Likert scale and nominal survey is used to obtain the aesthetic assessment of Lay persons. To come up with a conclusion the data gathered from the surveys and the assessment of the researcher is compared and analyzed. The qualities of the church with an excellent aesthetic result will be taken consideration in forming an aesthetic design guideline for a place of worship.